(untitled) (Third Sector Social Economic Review, 2024)
This research study delves into the intricate relationship between firm size and capital structure decisions in the context of the Turkish banking industry. Employing a comprehensive panel data approach, we meticulously collected 10 years of annual data encompassing key variables such as banks’ profitability, debt positions, size metrics, and macroeconomic indicators. By utilizing fixed effects panel regression analysis, we uncover significant insights. Our findings demonstrate that, specifically within the Turkish banking sector, the size of institutions, measured by log total assets, plays a crucial role in shaping capital structure decisions. Moreover, we identify bank size and inflation as influential factors in understanding the volatility surrounding these decisions. Surprisingly, we find that profitability and debt sensitivity ratios do not significantly contribute to explaining the variations in capital structure decisions among Turkish banks. These findings significantly enhance our understanding of the nuanced dynamics and determinants that drive capital structure decisions within the Turkish banking landscape.